Transformational leadership and safety management in Malaysia vocational colleges - Omar, Intan Marfarrina (Penerbit UTHM, 2022)
This study was an attempt to highlight the role of lecturers’ transformational leadership in determining safety management within the context of Malaysian Vocational Colleges. The research is quantitative research design which the sample consists of 302 final year students from eight different Vocational Colleges in Malaysia. An adapted questionnaire was used for data collection and it contained 100 items purposely constructed to assess lecturers’ transformational leadership and student’s safety management. The collected data were analyzed using SPSS 22 software to measure the analysis of Pearson correlation, linear regression and multiple regression. Results of the analysis revealed that lecturers’ transformational leadership is significantly and positively related to safety management. In addition, the study also revealed that student’s safety management has been affected 48.2 by lecturers’ transformational leadership practice. Overall, the research result can impact lecturers in the Vocational Colleges to review and enhance their leadership and provide a better understanding of transformational leadership behavior toward safety performance, safety training and safety climate that promote high-quality of safety management among students in future. © Universiti Tun Hussein Onn Malaysia Publisher’s Office.